Evaluation of First, Second and Third Generation Probe after Phase I Therapy in Chronic Periodontitis Patients- A Randomised Clinical Study - SA Jacob Raja; Johnson Raja James; Tamil Selvan Kumar; JP Mohan Raj; S Divya; P Fairlin; Gokulvathi Rajkumar; Maria Beulah (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Periodontitis manifested by the presence of periodontal pocket depth and loss of attachment level is detected and measured by using periodontal probes. Various generations of probes have been discovered and are used to measure the pocket depth. There has been a huge difference in the accuracy of different generations of probe. Aim: To compare the interprobe accuracy of first, second and third generations of probe on clinical parameters in patients with chronic periodontitis. Materials and Methods: This randomised comparative clinical study was conducted at the Department of Periodontics, Bapuji Dental College and Hospital, Davangere, Karnataka, India and included 30 chronic periodontitis patients, randomly allocated into three groups with each group consisting of 10 patients. The study was conducted over a period of eight months, from February 2001 to October 2001. Conventional periodontal probe, True Pressure Sensitive (TPS) probe and Florida probe were used to examine the patients. The probes were used in sequence of I, II and III for first 10 patients, II, III and I for next 10 patients and III, I and II for the last 10 patients to avoid bias due to examiner memory of clinical parameters. The recorded clinical parameters were Plaque Index (PI) (Silness and Loe 1964), Gingival Index (GI) (Loe and Silness 1963), Bleeding On Probing (BOP) index (Ainamo and Bay 1975), Probing Pocket Depth (PPD) and Clinical Attachment Level (CAL). At baseline, all the clinical parameters were recorded by two calibrated examiners i.e., Examiner-1 and Examiner-2. Examiner-I recorded all the clinical parameters postoperatively at Ist, IInd, IIIrd and IVth consecutive weeks. The statistical analysis was done using paired t-test, One-way Analysis of Variance (ANOVA), studentised range test and Karl Pearson’s correlation coefficient test for calculation and comparison of interexaminer and intraexaminer variability. Results: Among the 30 patients included in the present study, 22 were males and eight were females. The mean age of the patients involved in the study was 45.16±1.33 years. The mean value of PI and GI showed a statistically significant reduction at different intervals with a value of 0.16±0.21 and 0.22±0.21 postoperatively (4th week). The probing depths measured using Williams periodontal probe, TPS probe and Florida probe were reduced to 4.2±0.4 mm, 3.9±0.4 mm and 3.5±0.4 mm, respectively at the end of 4th week. The CAL measured using Williams periodontal probe, TPS probe and Florida probe were reduced to 7.0±0.6 mm, 6.6±0.5 mm and 6.1±0.6 mm, respectively at the end of 4th week. Conclusion: The TPS probe, Williams probe, and Florida probe showed their superiority regarding the accuracy of recording clinical parameters in the decreasing order respectively.